Analisis Minat Siswa Dalam Bermain Sepakbola Di SD Inpres Sarroangin Kecamatan Bungaya Kabupaten Gowa - Muhammad Harliawan; Hasyim Hasyim (Departement of Mathematics Education, 2023)
Interest is a tendency that lasts a long time towards an object or in carrying out an activity (action) which is based on feelings of interest, pleasure that arises from within. Interest plays a very important role in students' lives and has a big impact on attitudes and behavior. Students who are interested in learning activities will try harder than students who are less interested. Football is a game that is played by kicking the ball to and fro which is contested by the players with the aim of putting the ball into the opponent's goal and defending its own goal so that the ball does not concede. In playing the ball, each player is allowed all limbs, except for the hands and arms. The data collection method in this study uses a survey method with data collection techniques using a questionnaire/questionnaire. The results of this study are interest indicators that influence students in playing soccer by factors internal and external factors, interest indicators contribute as much as 14%, attention indicators 18%, activity indicators 14%, family indicators 16%, school indicators 20%, and environmental indicators 20%